NSTEMI Presenting with Acute Pulmonary Edema with Culprit Lession Total Occluced Left Circumflex: a case report - Budi Yuli Setianto; Nahar Taufiq; Heri Hernawan (ACI (Acta Cardiologia Indonesiana), 2015)
Current guidelines for the management of patients with acute coronary syndromes (ACSs) focus on the ECG to dichotomize patients into having ST elevation myocardial infarction (STEMI) or non-ST elevation myocardial infarction (NSTEMI)/ Unstable Angina (UA) in order to rapidly triagepatients to receive reperfusion therapy. Left circumfl ex artery occlusion is often categorized as NSTEMI because of the absence of signifi cant ST elevation on the 12 standard ECG leads. ST elevation is the condition ‘sine qua non’ for diagnosing acute total coronary occlusion causing transmural infarction. However, ST elevation when there is circumfl ex artery occlusion is seen onthe 12 standard ECG leads in fewer than 50% of patients. We reported a 77 years old women who diagnosed with NSTEMI. Twelve lead ECG showed ST depressed in V2-V5. On angiography we found a totaly ocluded of left circumfl ex as culprit lession.Keywords: NSTEMI; culprit lession; total occlusion; left circumflex artery